2007
DOI: 10.1002/pros.20699
|View full text |Cite
|
Sign up to set email alerts
|

Galiellalactone is a novel therapeutic candidate against hormone‐refractory prostate cancer expressing activated Stat3

Abstract: Galiellalactone induced growth inhibition and apoptosis in androgen-insensitive PCa cells expressing p-Stat3. We suggest that galiellalactone is a potential anti-tumor lead against hormone-refractory PCa with constitutively active Stat3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 47 publications
4
75
0
Order By: Relevance
“…This demonstrates that galiellalactone is not specific for STAT3, although the identification of STAT3 as a direct binding target correlates well with the inhibitory effects seen in galiellalactone-treated DU145 cells expressing constitutively active STAT3. In addition, galiellalactone has been shown to be well tolerated in animal studies with repeat dosing and displays minimal cytotoxic effects in non-STAT3-dependent cells, which would not be expected with a non-discriminate and highly reactive compound (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrates that galiellalactone is not specific for STAT3, although the identification of STAT3 as a direct binding target correlates well with the inhibitory effects seen in galiellalactone-treated DU145 cells expressing constitutively active STAT3. In addition, galiellalactone has been shown to be well tolerated in animal studies with repeat dosing and displays minimal cytotoxic effects in non-STAT3-dependent cells, which would not be expected with a non-discriminate and highly reactive compound (20).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that galiellalactone inhibits the growth, both in vitro and in vivo, of prostate cancer cells expressing activated STAT3 and inhibits the expression of STAT3-regulated genes and proteins (20). Furthermore, galiellalactone inhibits growth and induces apoptosis of prostate cancer stem cell-like cells expressing phosphorylated STAT3 (pSTAT3) (21).…”
mentioning
confidence: 99%
“…Moreover, this agent induced growth inhibition of human prostate (DU145) tumor xenografts delivered at 3 mg/kg per day intra-peritoneally [94], a promising in vivo activity and effect.…”
Section: Inhibitors Targeting the Stat3 Dna-binding Domainmentioning
confidence: 98%
“…Galiellalactone (Weidler et al, 2000;Hellsten et al, 2008), flavopiridol (Lee et al, 2006) and a class of platinum (IV) compounds including IS3295 (Turkson et al, 2005), CPA-1, CPA-7 and platinum (V) tetrachloride (Turkson et al, 2004b), and decoy oligodeoxynucleotides (Xi et al, 2005;Zhang et al, 2007;Gu et al, 2008;Sun et al, 2008;Zhang et al, 2010;Barton et al, 2004) were found to interfere with Stat3 binding to DNA as well as induce cell growth inhibition and apoptosis of human breast, lung and prostate cancer cells (Hellsten et al, 2008;Barton et al, 2004;Zhang et al, 2010;Zhang et al, 2007;Xi et al, 2005;Sun et al, 2008;Gu et al, 2008;Turkson et al, 2004b;Turkson et al, 2005;Lee et al, 2006). Some of these inhibitors have been tested in animal models and they appear to cause regression of xenograft tumors.…”
Section: Stat3 Transcription Factormentioning
confidence: 99%